Dynamic hand orthoses for the recovery of hand and arm function in adults after stroke: A systematic review and meta-analysis of randomised controlled trials. Issue 2 (17th February 2022) - Alexander, Jen; Dawson, Jesse; Langhorne, Peter
ABSTRACT: Background: Repetitive, functional-based rehabilitation is recommended after stroke. However, impaired active digital extension is common after stroke, which limits functional-based rehabilitation and recovery. Non-robotic dynamic hand orthoses (DHOs) may address this. Objectives: We did a systematic review and meta-analysis to determine whether non-robotic DHOs improve upper limb recovery after stroke in comparison to i)placebo or no intervention and ii)usual care. Methods: We followed PRISMA guidelines. We included randomized controlled trials (RCTs) assessing upper limb recovery associated with the use of non-robotic DHOs in adults after stroke. Outcomes of interest were functional upper limb movement and activities of daily living. We performed searches on 27 September 2019 in 10 bibliographic databases including Cochrane Stroke Groups Specialized Trials Register and Cochrane Central Register of Controlled Trials. We also searched gray literature and citations from included studies. Two reviewers independently screened abstracts and full text, extracted data and assessed risk of bias using a Cochrane risk of bias tool. Results: We reviewed 7225 titles and included four studies involving 56 randomized participants, all with a high risk of bias. A positive effect in favor of non-robotic DHOs was observed for two outcomes; upper limb function (mean difference (MD) 6.23, 95% confidence interval (CI) 0.28–12.19 ( p = 0.04)) and dexterity (MD 2.99, 95% CI 0.39–5.60 ( p = 0.02). Conclusions: The results are encouraging but included studies were small with high risk of bias meaning there is currently insufficient evidence that non-robotic DHOs improve upper limb recovery after stroke. Review Registration: PROSPERO, CRD42020179180. Registered on 20 May 2020.